A DESIGN OF SALES INFORMATION SYSTEM ON PAPER CUTTING MACHINE DISTRIBUTOR - Permatasari, Angelina (Bina Nusantara University, 2011)
The purpose of this research is to analyze the problems that exist in a company engaged in the sales of paper cutting machine that is on sale systems that are running on the company, identifying the needs of enterprise information and designing information systems that are able to meet the company’s information needs. The used methodology is the method of analysis and design methods. The analysis method is library research, observation, survey of the old system, the identification of information needs and interviews. While the design method used is Object Oriented Analysis and Design (OOAD).The achieved results are in the form of sales information system for paper cutting machine distributor in the form of application design to improve the sales system, which is still done manually. The conclusion is a computerized information system sales can solve problems that occur on the old systems and procedures in the company.Keywords: Design; Sales Information System